Determination of anthropometric indicators of the hand of athletes on the basis of computer vision - Pomerantsev, A. A.; Bespyatkin, V. E.; Travkov, D. A.; Bakhtiarova, T. V. (Theory and Practice of Physical Culture, 2023)
In most sports, athletes interact with the outside world through various grips: holding their own weight (hanging on the bar, standing on the uneven bars), holding equipment (racquet, ball, paddle) or interacting with an opponent (martial arts). The linear dimensions of the hand in many sports determine the success of competitive activity. So, weightlifters have a longer hand than the average person, as this contributes to a stronger grip on the bar. In handball, a large brush size contributes to a stronger hold on the ball. Despite the long history of studying the anthropometry of the hand, the classical methods are still the main methods for changing its parameters - measurements using a centimeter tape and a ruler.